Weak-beam scanning transmission electron microscopy for quantitative dislocation density measurement in steels. (18th January 2017) - Yoshida, Kenta; Shimodaira, Masaki; Toyama, Takeshi; Shimizu, Yasuo; Inoue, Koji; Yoshiie, Toshimasa; Milan, Konstantinovic J.; Gerard, Robert; Nagai, Yasuyoshi
Abstract: To evaluate dislocations induced by neutron irradiation, we developed a weak-beam scanning transmission electron microscopy (WB-STEM) system by installing a novel beam selector, an annular detector, a high-speed CCD camera and an imaging filter in the camera chamber of a spherical aberration-corrected transmission electron microscope. The capabilities of the WB-STEM with respect to wide-view imaging, real-time diffraction monitoring and multi-contrast imaging are demonstrated using typical reactor pressure vessel steel that had been used in an European nuclear reactor for 30 years as a surveillance test piece with a fluence of 1.09 × 10 20 neutrons cm – 2 . The quantitatively measured size distribution (average loop size = 3.6 ± 2.1 nm), number density of the dislocation loops (3.6 × 10 22 m −3 ) and dislocation density (7.8 × 10 13 m m – 3 ) were carefully compared with the values obtained via conventional weak-beam transmission electron microscopy studies. In addition, cluster analysis using atom probe tomography (APT) further demonstrated the potential of the WB-STEM for correlative electron tomography/APT experiments.